Probing residual stress evolution of titanium alloy due to belt grinding based on molecular dynamics method. (June 2021) - Zhou, Kun; Liu, Jinfei; Xiao, Guijian; Huang, Yun; Song, Kangkang; Xu, Jiayu; Chen, Benqiang
Graphical abstract: Highlights: Ti atoms were tracked to record their displacement and momentum during cutting. Grain affected its front Ti atoms in the form of oscillation and diffusion. Ti molecule below the grain deformed elastically in-depth direction. Ti atoms close to the cutting surface moved faster during cooling. Residual compressive stress occurred in the area ahead of grain escaping. Abstract: Belt grinding is widely used as the final manufacturing step for the titanium alloy components to obtain excellent surface integrity, and the residual stress after grinding is one of the most concerning issues. However, the formation and evolution of residual stress due to belt grinding have not been well understood for a long time. In this study, a molecular dynamics (MD) model of abrasive grain cutting was established, and the titanium atoms were dynamically tracked from the beginning of cutting to the end of cooling to investigate the residual stress. The results show that the titanium atoms on both sides and underneath the abrasive grain showed different deformation patterns; besides, the titanium atoms close to the cutting surface moved faster during cooling than those far from the cutting surface, which eventually resulted in the initiation of residual stress. In addition, the residual stresses in the depth direction were primarily compressive stress, and those parallel to the cutting direction were tensile stress. Furthermore, a high-level residual compressive stress was found in the area ahead of the position of abrasive grain escaping, though the area did not contact the abrasive grain directly.